Doping and Reproductive Health in Female Athletes: A Narrative Literature Review - Dafa Wishnu Moerara; Muhammad Rafi Zulfikar; Muhammad Arief Setiawan; Aprillia Wulan Utari; A. Ine Aprilia Damai (Universitas Negeri Semarang, 2026)
Doping is not only a violation of sport integrity but also a health-risk behaviour with specific implications for female athletes. This narrative literature review synthesises peer-reviewed studies, consensus statements, and official anti-doping documents published mainly between 2014 and 2026. The review focused on prohibited substances and methods that may affect endocrine regulation, menstrual function, fertility potential, virilisation, sexual health, and athlete well-being. The strongest evidence concerns anabolic-androgenic steroids, which can disrupt the hypothalamic-pituitary-ovarian axis, impair ovulation, cause oligomenorrhea or amenorrhea, reduce fertility potential, and produce androgenic changes such as acne, hirsutism, voice deepening, breast atrophy, and clitoromegaly. Human growth hormone, stimulants, hormone modulators, diuretics, and masking practices may contribute to reproductive-health risk indirectly through metabolic disturbance, cardiovascular strain, neuroendocrine stress, appetite suppression, low energy availability, and substance stacking. Menstrual dysfunction should not be interpreted as direct proof of doping because relative energy deficiency in sport, psychological stress, training load, eating disorders, pregnancy, and endocrine disease may produce overlapping symptoms. Prevention therefore requires gender-responsive anti-doping education, confidential medical referral, menstrual-health monitoring, supplement-risk counselling, therapeutic-use guidance, psychological support, and consistent anti-doping control. The review concludes that clean-sport policy should be integrated with reproductive-health protection so that female athletes receive both fair-competition safeguards and clinically appropriate support.